Incidence of and risk factors for Motor Neurone Disease in UK women: a prospective study - Doyle Pat; Brown Anna; Beral Valerie; Reeves Gillian; Green Jane (BMC Neurology, 2012)
Abstract Background Motor neuron disease (MND) is a severe neurodegenerative disease with largely unknown etiology. Most epidemiological studies are hampered by small sample sizes and/or the retrospective collection of information on behavioural and lifestyle factors. Methods 1.3 million women from the UK Million Women Study, aged 56 years on average at recruitment, were followed up for incident and/or fatal MND using NHS hospital admission and mortality data. Adjusted relative risks were calculated using Cox regression models. Findings During follow-up for an average of 9·2 years, 752 women had a new diagnosis of MND. Age-specific rates increased with age, from 1·9 (95% CI 1·3 – 2·7) to 12·5 (95% CI 10·2 – 15·3) per 100,000 women aged 50–54 to 70–74, respectively, giving a cumulative risk of diagnosis with the disease of 1·74 per 1000 women between the ages of 50 and 75 years. There was no significant variation in risk of MND with region of residence, socio-economic status, education, height, alcohol use, parity, use of oral contraceptives or hormone replacement therapy. Ever-smokers had about a 20% greater risk than never smokers (RR 1·19 95% CI 1·02 to 1·38, p = 0·03). There was a statistically significant reduction in risk of MND with increasing body mass index (pfor trend = 0·009): obese women (body mass index, 30 kg/m2 or more) had a 20% lower risk than women of normal body mass index (20 to <25 Kg/m2)(RR 0·78 95% CI 0·65-0·94; p = 0·03). This effect persisted after exclusion of the first three years of follow-up. Interpretation MND incidence in UK women rises rapidly with age, and an estimated 1 in 575 women are likely to be affected between the ages of 50 and 75 years. Smoking slightly increases the risk of MND, and adiposity in middle age is associated with a lower risk of the disease.